ACTIVE LEARNING METHODS: THE CASE METHOD AND ITS ROLE IN STUDENTS' PROFESSIONAL TRAINING - Rahmanova Sayyora Rajabovna (Western European Studies, 2024)
Active learning methods, particularly the case method, play a pivotal role in enhancing students' professional training by fostering critical thinking, problem-solving, and decisionmaking skills. The case method immerses students in real-life or simulated scenarios, encouraging them to apply theoretical knowledge in practical contexts relevant to their fields, such as law, business, medicine, and education. By actively engaging in discussions, collaborative problem-solving, and leadership exercises, students develop the essential skills needed to navigate complex, real-world challenges, effectively bridging the gap between academic theory and professional practice.
Keywords: Active learning; Case method; Professional training